Nonmedical Use of Prescription Opioids among Adolescents: Subtypes Based on Motivation for Use - Young, Amy (2012)
The purpose of this study was to advance our understanding of nonmedical use of prescription medications by identifying distinguishing characteristics of two subtypes of adolescent nonmedical users of prescription opioids described by Boyd and McCabe(1). A web-based, self-administered survey was completed by 2,597 7(th) – 12(th) grade students. Sensation seeking nonmedical users were best characterized by rule breaking and aggressive behaviors and possible substance dependence. Medical users and nonmedical self treating users were best characterized by somatic complaints, anxiety/depressive symptoms, and history of sexual victimization.